Characteristics and success factors of rural community leadership in Malaysia: a focus group analysis - Md Rami, Ahmad Aizuddin; Abd Aziz, Mohd Faiq; Muhamad Nasharudin, Nurfazreen Aina; Mohd Rasdi, Roziah (Universiti Putra Malaysia Press, 2021)
The leadership aspects of rural leaders in Malaysia are still unclear, and a consensus of the characteristics of credible rural community leaders has not been achieved. In addition, there is still a lack of specific and in-depth research on community leadership in rural areas in Malaysia. Therefore, a study was conducted to deepen understanding of leadership, specifically in the rural community leadership characteristics and success factors. The current study used a qualitative approach via a focus group discussion method involving 15 informants from the Village Development and Security Committee (JPKK) to gain in-depth information. The major themes that emerged from findings include inborn leadership, leadership quality, leadership characteristics, leadership motivation, and leadership training, referred to as leaders’ success factors. The current study hopes that the government can provide focused and comprehensive leadership training programs to ensure leaders perform their duties effectively and efficiently.